Water temperature modulates multidimensional plastic responses to water flow during the ontogeny of a neotropical fish (Astyanax lacustris, characiformes) - Lofeu, Leandro; Bonini-Campos, Bianca; Kohlsdorf, Tiana (Frontiers in Cell and Developmental Biology, 2025)
IntroductionPlastic phenotypes result from multidimensional developmental systems responding to distinct yet simultaneous environmental signals, which may differently affect the magnitude and directions of plastic responses.Concomitant environmental signals during development may result in dominant, synergistic, or even antagonistic phenotypic effects, so that a given condition may amplify or minimize plastic responses to other environmental stimuli. Knowledge on how external information shapes complex plastic phenotypes is essential to predict potential evolutionary trajectories driven by developmental plasticity.MethodsHere, we manipulate water temperature to evaluate its effects on the well-described phenotypic accommodation of fish growth in the presence of water flow, using the neotropical species Astyanax lacustris. We include larval and juvenile ontogenetic stages to examine the interaction between these two environmental signals in plastic responses related to body size and shape, skeleton ossification and gene expression, using bmp4 as a proxy for ossification pathways.Results and discussionOur results demonstrate that water temperature plays a crucial role determining the expression of plastic variation at all dimensions, and effects of water flow were restricted to specific thermal regimes. Combination of high temperature and water flow has a major effect on body shape and unveils unique phenotypic patterns, supporting the prediction that high temperatures can amplify plastic responses to external signals. Specifically, fish raised in the presence of water flow at warmer environments grew faster and ossified earlier, and this condition increased bmp4 expression levels especially at later developmental stages. Such plastic phenotypes likely involve a functional relationship with swimming performance in running-water environments. Our findings highlight the importance of studying developmental plasticity in complex environments using a multidimensional approach, especially considering increments in water temperatures due to accelerated climate changes that likely impact the fish developmental potential to mitigate environmental changes through plastic responses.